Raising the voices of Pacific Island women to inform climate adaptation policies. (July 2018) - Mcleod, Elizabeth; Arora-Jonsson, Seema; Masuda, Yuta J.; Bruton-Adams, Mae; Emaurois, Carol O.; Gorong, Berna; Hudlow, C.J.; James, Robyn; Kuhlken, Heather; Masike-Liri, Barbara; Musrasrik-Carl, Emeliana; Otzelberger, Agnes; et al.
Abstract: Policymakers and natural resource managers are increasingly recognizing the importance of broader geographic and gender participation in assessing climate vulnerability and developing effective adaptation policies. When such participation is limited, climate mitigation and adaptation polices may miss key opportunities to support vulnerable communities, and thus inadvertently reinforce the vulnerability of marginalized groups. This paper reports rich qualitative data from women leaders in conservation, development and climate adaptation projects to support local communities across seven Pacific Island nations. The results indicate the following priorities to support climate adaptation policies in the Pacific: (1) increased recognition for the importance of traditional knowledge; (2) greater support for local women's groups, including strategic planning and training to access climate finance mechanisms; and (3) climate policies that consider alternative metrics for women's empowerment and inclusion, formalize women's land rights, and provide land for climate refugees. Existing evidence is discussed which supports the importance of these priorities in the Pacific. Their input identifies research gaps in climate adaptation and provides important guidance for governments, non-governmental organizations, and development agencies leading climate adaptation efforts. Highlights: Pacific Island women are leading innovative adaptation projects building on traditional knowledge. Pacific Island women have critical insight to inform equitable and inclusive climate policies. Participation, power, and gender are key considerations for equitable climate policies. Climate policies are needed that consider alternative metrics for women's empowerment.